The effects of soil management practices on soil organic matter changes within a productive vineyard in the Nitra viticulture area (Slovakia) - Šimanský Vladimír; Polláková Nora (Agriculture, 2016)
Since understanding soil organic matter (SOM) content and quality is very important, in the present study we evaluated parameters of SOM including: carbon lability (LC), lability index (LI), carbon pool index (CPI) and carbon management index (CMI) in the soil as well as in the water-stable aggregates (WSA) under different soil management practices in a commercial vineyard (established on Rendzic Leptosol in the Nitra viticulture area, Slovakia). Soil samples were taken in spring during the years 2008–2015 from the following treatments: G (grass, control), T (tillage and intensive cultivation), T+FYM (tillage + farmyard manure), G+NPK3 (grass + 3rd intensity of fertilisation for vineyards), and G+NPK1 (grass + 1st intensity of fertilisation for vineyards). The highest LI values in soil were found for the G+NPK3 and T+FYM fertilised treatments and the lowest for the unfertilised intensively tilled treatments. The CPI in the soil increased as follows: T < G+NPK3 < T+FYM < G+NPK1. The highest accumulation of carbon as well as decomposable organic matter occurred in G+NPK1 compared to other fertilised treatments, while intensive tillage caused a decrease. On average, the values of LI in WSA increased in the sequence G+NPK1 < T+FYM < G+NPK3 < T. Our results showed that the greatest SOM vulnerability to degradation was observed in the WSA under T treatment, and the greatest values of CPI in WSA were detected as a result of fertiliser application in 3rd intensity for vineyards and farmyard manure application.